A Comprehensive Review of the Phytochemical Constituents and Bioactivities of Ocimum tenuiflorum - Keshab Bhattarai; Rabin Bhattarai; Ram Darash Pandey; Babita Paudel; Hari Datta Bhattarai (The Scientific World Journal)
Ocimum tenuiflorum, commonly known as Tulsi, is revered in Ayurveda for its extensive medicinal properties. However, there is a need to consolidate current knowledge on its phytochemical constituents and their pharmacological activities to identify potential areas for further research and drug development. This review aims to bridge this gap by providing a comprehensive analysis of the bioactive secondary metabolites found in O. tenuiflorum, such as rosmarinic acid, oleanolic acid, luteolin, ursolic acid, and limonene, and their associated therapeutic effects. The review will highlight the pharmacological importance of these metabolites, which exhibit antioxidant, neuroprotective, anticancer, and anti-inflammatory properties. Additionally, this study will explore the plant’s wide range of beneficial qualities, including anti-inflammatory, antioxidant, anticholinergic, pain-relieving, antimicrobial, stress-reducing, antidiabetic, anticancer, liver-protective, ulcer-inhibiting, antifungal, and wound-healing attributes. Furthermore, this review focuses on the plant’s potential in treating conditions such as asthma, persistent fever, tuberculosis, malaria, skin discoloration, itching, digestive issues, hemorrhoids, bone fractures, gout, urinary tract infection, and diabetes. By reviewing the current literature, the aim is to identify the gaps in the existing research and propose directions for future studies. This comprehensive review will serve as a valuable resource for researchers in the development and investigation of novel drugs derived from O. tenuiflorum.